Addition of trastuzumab emtansine (T-DM1) in a human epidermal growth factor receptor 2–overexpressed metastatic carcinoma of the gallbladder patient to enhance survival: A case study. (November 2022) - Lavingia, Viraj; Thummar, Vipulkumar; Mehta, Priya
Biliary tract cancers are clinically and genetically heterogeneous cancer type with a worst prognosis among gallbladder adenocarcinoma patients. Systemic therapeutic options for metastatic biliary tract cancers are fewer, and there are limited treatment choices for the patients who progress on first line apart from symptomatic treatment. Thus, a biomarker-guided personalized treatment approach needs to be explored among biliary tract cancer subtypes. We encountered a case of 53-year-old male patient with human epidermal growth factor receptor 2 (HER2, ERBB2) positive metastatic gallbladder cancer, treated with first-line gemcitabine and cisplatin combination–based chemotherapy along with trastuzumab followed by second-line treatment with mFOLFIRINOX. On progression in third line, treated with single agent ado-trastuzumab emtansine targeting human epidermal growth factor receptor 2 and got survival benefit of nearly 6 months. This is the first reported case from India that explored the possibility and impact of ado-trastuzumab emtansine in advanced gallbladder cancer after exhausting standard treatment options. It highlights the possibility of exploring ado-trastuzumab emtansine for treatment resilient, human epidermal growth factor receptor 2-positive and advanced gallbladder adenocarcinoma.